The prevalence and risk factors of diabetes and hypertension among police personnel: A population-based cross-sectional study - Deepak V. Chaturvedi; Digant Gupta; Darpan M. Maheshgauri; Gauri E. Yadav; Dhrubajyoti J. Debnath; Asmita D. Chaturvedi (Journal of Family Medicine and Primary Care)
Background: Police personnel represent a special occupational group who because of the nature of their jobs are at an increased risk of lifestyle disorders such as diabetes and hypertension. Although studies have been conducted to assess the health status of police personnel in India, most of them suffer from small sample sizes, selection bias, and poor generalizability. Objectives: This large-scale study evaluated the prevalence of diabetes and hypertension along with their risk factors among police personnel in Mumbai, India. Methods: A population-based cross-sectional study was conducted in 3474 police personnel. The key risk factors of interest were age, gender, and body mass index (BMI). Binary logistic regression was used to quantify the relationship between the independent variables (age, gender, and BMI) and the dichotomous dependent variables (diabetes and hypertension). Results: 86.3% were males while 13.7% were females. The mean age was 41.6 years. In total, 48.7% of participants were overweight while 19.9% were obese. Totally, 29.2% of participants were pre-diabetic/diabetic and 55.2% were hypertensive. Using adjusted logistic regression, participants with > = 55 years were 7.9 and 3.7 times more likely to have diabetes and hypertension respectively compared to those with < = 34 years. Similarly, obese individuals were 1.6 and 3.1 times more likely to have diabetes and hypertension respectively compared to those with normal BMI. Conclusions: This study demonstrates a high prevalence of cardiovascular risk factors such as diabetes, hypertension, and obesity among Indian police personnel and provides the scientific basis for planning interventional strategies to improve their health.